Two new species of Phareicranaus Roewer, 1913 (Opiliones: Laniatores: Cranaidae), with notes on gregarious behavior and maternal care in Phareicranaus manauara - Colmenares, Pío A. (Zootaxa, 2020)
In this paper we describe two new species of Phareicranaus Roewer, 1913: Phareicranaus rohei sp. nov. from the state of Amazonas, Brazil and Phareicranaus tizana sp. nov., from the state of Zulia, Venezuela. The number of known species of this genus increases to 47. We discuss and suggest the possible relationships of these species with their relatives and assign them into the clades proposed by Pinto-da-Rocha & Bonaldo (2011). Additionally, we conducted field observations at the type locality of Phareicranaus manauara (Pinto-da-Rocha, 1994), provide the first descriptions of maternal care and gregarious behavior, and discuss the occurrence of this behavior in the genus. Copyright © 2014 Magnolia Press.